Knowledge and attitude of Malaysia’s Muslim faith healers in dealing with the mentally ill - Md. Sa’ad, R.A.; Razali Z.A.; Mohd Rani M.D.; Suhaila Sanip (Routledge, 2024)
Muslim faith healers are often sought by the Malaysian public as an avenue to address psychological distress. “Ruqyah” refers to the recitation of verses from the Qur'an and/or sayings of Prophet Muhammad (PBUH) and is used by Muslim faith healers as a method of treatment. This study was conducted to assess the knowledge and attitude of Muslim faith healers in dealing with psychiatric patients in Malaysia. Seven Muslim faith healers were interviewed. The interviews were transcribed verbatim, and analysed qualitatively using thematic content analysis. The authors identified four themes: understanding of psychiatric illnesses, diagnostic competence, patients' referral, and integrating “ruqyah” into mainstream psychiatry. It was found that the respondents had limited knowledge of psychiatric illness, focusing on “ruqyah” as the main intervention in treating psychiatric illness. Recognizing the important role played by Muslim faith healers in the treatment of psychiatric illness in Malaysia, collaboration between them and fellow psychiatrists is deemed highly necessary.